RISIKO KESEHATAN PAPARAN KERJA TERHADAP BAHAN KIMIA BERACUN DI TEMPAT KERJA TAMBANG BATUBARA - Widatul Jannah; Susilawati (Jurnal Kesehatan, 2024)
Mining is the most dangerous occupational sector in the world. Based on statistical data from the Ministry of Energy and Mineral Resources, during 2019 there were mining accidents which resulted in the death of 24 people, 105 workers heavy and 28 workers light. The cause of work accidents in the workforce is related to exposure to underground mining toxic gases. This study used the Literature Review (LR) methodology where the data source was obtained from "Scopus" with search keywords the year of publication was limited from 2019 - 2023. From a literature review, predeposition factors consisting of age, work experience, work location and body parts have an effect on work accidents in workers, risk assessment factors are the most important factors applied to prevent work accidents in the workplace and the role of the company in influencing work accidents. Based on the research questions, it can be concluded that the causes of work accidents include: lack of knowledge and motivation in using personal protective equipment and not carrying out work permit compliance procedures, not using personal protective equipment and not having a work permit socialization. Factors such as worker age, work experience are not positively correlated with work accidents while work location and body parts influence the causes of work accidents. Risk assessment factors can be carried out to minimize the occurrence of work accidents. In addition, it is known that many companies have prioritized safety issues as evidenced by the many studies conducted by companies to prevent work accidents in the workforce.